Navigating Sharia Compliance in the Digital Age: An Examination of Bank Indonesia’s Hedging Swap Regulation (PBI 24/7/2022) - Anggraeni, Sinta Thia; Bukhari, Imran; Dahmayanti, Andi (Indonesian Journal of Islamic Economic Law, 2025)
The present study aims to examine the alignment of Islamic values with the principles of efficiency and profitability, as contained in Bank Indonesia's Hedging Swap regulation, to ensure innovation in the digital financial sector. The objective of this study is to ascertain how the integration of contemporary banking law with fiqh can establish a framework that facilitates the development of Shariah compliant digital financial products that comply with financial law based on Islamic principles without compromising the capacity of banks to generate profits. This research adopted a qualitative methodology and a literature study approach, employing data processing techniques to collect and evaluate pertinent literature on digital financial products and Islamic jurisprudence. The data triangulation method was applied by sorting and extracting through a deductive approach to data interpretation specific to the research objectives. The study concluded that the al-tahawwuth al-murakkab contract successfully integrates Islamic principles, bank profits and the dynamics of the digital era. However, the approach is only relevant for commercial banks and does not fully support digital transformation in micro scale banks.